2007
DOI: 10.1007/s00455-006-9071-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dysphagia in Toxic Epidermal Necrolysis (TEN) and Stevens-Johnson Syndrome (SJS)

Abstract: Toxic epidermal necrolysis (TEN) is a rare and potentially fatal skin disorder, precipitated by severe allergic drug reaction, and is one of a spectrum of conditions, which includes Stevens-Johnson syndrome (SJS). Mucosal involvement is common, resulting in extreme pain on swallowing and poor oral intake. The aim of this study was to describe swallow function in TEN and SJS and define the role of Speech Pathology in management. The Burns Unit database was reviewed for patients that presented over a five-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…12,14 The extensive erosions and haemorrhagic crusting can interfere oral functions causing odynophagia, inability to tolerate solid foods, and increased aspiration risk. 12,15 All the clinical manifestations of SJS/ TEN overlap in our patient is concordant with the literature explained above.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…12,14 The extensive erosions and haemorrhagic crusting can interfere oral functions causing odynophagia, inability to tolerate solid foods, and increased aspiration risk. 12,15 All the clinical manifestations of SJS/ TEN overlap in our patient is concordant with the literature explained above.…”
Section: Discussionsupporting
confidence: 92%
“…17 Specific oral care strategies can be used to minimize trauma during oral functions such as using smaller utensils and syringes. 15 Corticosteroids play a central role in the treatment of vesiculo erosive oral lesions of autoimmune and or immunologically mediated diseases, but the evidence for the efficacy of TC in oral medicine is limited, and many of the protocols followed are drawn from experience gained in a dermatological use. 17 Those major challenges becomes more problematic as there are very few commercial products are currently available for the topical treatment of the oral mucosal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…PN appears to be recommended due to concern that the extensive epithelial loss in SJS/TEN affects the entire gastrointestinal tract and results in poor absorption and intolerance as well as difficulty placing enteral feeding tubes 2 , 14 16 . Studies frequently note oral mucosal involvement that causes sloughing and associated pain 2 , 14 , 17 . Clayton and Kennedy reviewed dysphagia rates in patients with SJS/TEN 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies frequently note oral mucosal involvement that causes sloughing and associated pain 2 , 14 , 17 . Clayton and Kennedy reviewed dysphagia rates in patients with SJS/TEN 14 . They reported that 86% of their study group had mucosal involvement, with nearly all (93%) complaining of odynophagia.…”
Section: Discussionmentioning
confidence: 99%
“…Phimosis can occur in men [41]. Bronchopulmonary complications confer a poor prognosis and include chronic bronchitis, bronchiolitis obliterans, bronchiolitis obliterans with organizing pneumonia, bronchiectasis [42], [43] Oesophageal stricture and webbing has also been described and can result in dysphagia [44]. …”
Section: Clinical Presentationmentioning
confidence: 99%